Noise Removal Pada Citra Digital Dengan Menggunakan Metode Active Contour - Randika Setyansyah; Yunita Sari Siregar; Mufida Khairani (UIN Sumatera Utara, 2021)
Disturbance in the image, especially digital images can be caused by noise, resulting in a decrease in the quality of the image. Image restoration is a technique used to recover the original image from a degraded image. Restoration is intended so that the information contained in a digital image becomes better/clear. The restoration process is carried out because the image quality is blurred or because of the noise contained in the image. Noise is the main problem encountered in digital image processing. The digital image restoration process always involves a filtering algorithm that is able to suppress the noise contained in the image. The active contour method is one approach to segmentation, where this method uses a closed curve that can move wide or narrow. The active contour process is a process that takes some of the signals of a certain frequency and discards signals at other frequencies. An initialization curve is placed outside of the object to be segmented, then through the iteration process the curve will move closer to the boundary of the object until finally finding the object boundary. This study aims to design a special system for character restoration in digital images using the active contour method. The implementation results show that the active contour method can be used to restore the image properly, this can be from the restored image, the condition of the image that has been given noise can approach the initial data. Keywords: active contour, digital image, character, restoration